The Production of Meanings on the Political Crisis in the Profissão Repórter Program - Conrad, Kalliandra Quevedo; Flores, Natália Martins; Fossá, Maria Ivete Trevisan (Brazilian journalism research, 2017)
We analyze the production of meanings on the Brazilian political crisis in Rede Globo’s television program Profissão Repórter. Based on the Critical Discourse Studies and Social Theory of Discourse, Fairclough (2016), we focus on the discursive strategies used by the program in its Political Crisis edition (04/06/2016). The use of categories of vocabulary analysis, interactive control and intertextuality allowed us to locate regionalizations of meanings that form a Workers Party (PT) subject position, a worker subject position and a protester subject position. The Workers Party subject establishes an antagonistic relation with the protester subject and marks itself by conflict, tension and fear meanings. The protester subject is built by respect, education, defense of the motherland and fight against corruption meanings. The worker subject appears in an intermediate region, not linked to the protests. The discourse silences the meanings of "impeachment" and "coup", and, therefore, avoids addressing the complexity of the Brazilian political crisis. Analisamos a produção de sentidos sobre a crise política brasileira no programa Profissão Repórter, da Rede Globo. A partir dos Estudos Críticos do Discurso e da Teoria Social do Discurso, de Fairclough (2016), nos focamos nas estratégias discursivas utilizadas pelo programa na edição Crise Política (6/04/2016). O uso das categorias de análise de vocabulário, controle interacional e intertextualidade permitiu localizarmos regionalizações de sentido nas posições de sujeito petista, sujeito trabalhador e sujeito manifestante. O sujeito petista estabelece uma relação antagônica com o sujeito manifestante e é marcado pelos sentidos de conflito, tensão e medo. O sujeito manifestante é construído pelos sentidos de respeito, educação, defesa da pátria e luta contra a corrupção. O sujeito trabalhador aparece numa região intermediária, não sendo vinculado aos protestos. O discurso silencia os significados de “impeachment” e “golpe”, eximindo-se de abordar a complexidade da crise política brasileira. Analizamos la producción de sentidos sobre la crisis política brasileña en el programa Profissão Repórter, da Rede Globo de Televisión. A partir de los Estudios Críticos del Discurso y de la Teoría Social del Discurso, de Fairclough (2016), nos centramos en las estrategias discursivas utilizadas por el programa en la edición de Crisis Política (06/04/2016). El uso de las categorías de análisis de vocabulario, control interactivo e intertextualidad nos ha permitido localizar regionalizacións de significado en torno de posiciones de sujetos de sujeto PT, sujeto trabajador y sujeto manifestante. El sujeto PT establece una relación antagónica con el sujeto manifestante y está marcado por significados de conflicto, tensión y miedo. El sujeto manifestante se construye a partir de sentidos de respeto, educación, defensa nacional y lucha contra la corrupción. El sujeto trabajador aparece en una región intermedia, al no estar relacionado con las protestas. El discurso silencia los significados de "impeachment" y "golpe", eximiendo se a abordar la complejidad de la crisis política brasileña.